The Use of Instagram Picture Series as Media to Improve Students’ Ability in Writing Procedure Text - Vebriary Eka Rahmawati; Sulistyaningsih (JournEEL, 2020)
This research aims to know whether the students’ ability in writing procedure text could be improved through the use of Instagram picture series as teaching media. This is a classroom action research (CAR) implemented in two cycles, on the eleventh-grade students of Madrasah Aliyah NU Sidoarjo in 2019/2020 academic year. This research uses quasi-experimental design which has these criteria based on Mueller: 1). No random selection of subjects; 2). Pre-test both groups; 3). Experimental group receives new treatment; 4). Control group receive no treatment or the normal treatment; 5). Post-test both groups. The population is 126 students. The samples are ten students of XI MIPA 1 as the experimental group and ten students of XI MIPA 2 as the control group. The independent variable is Instagram picture series as media of teaching writing. The dependent variable is the students’ ability in writing procedure text. In collecting the data, the researcher applied instrument: interview, questionnaire, Instagram application, writing pre-test and writing post-test. The data was analyzed statistically using T-test. The researcher examines two cycles of test. As the result in the first cycle, the pre-test average score of the control group is 44 and the experimental group is 45.5. In the first cycle of pot-test, the average score of the control group is 70 and the experimental group is 78. Both of them don’t get the Kriteria Ketuntasan Minimum (KKM) or the level of basic competence score which is 80. So, the second cycle of post-test is held. As the result, the average score of the control group is 74 and the experimental group is 82.5. The next cycle of post-test isn’t needed because the average score of the experimental group is already passed over the KKM. It means that, the use of Instagram picture series as teaching media has the significant positive impact to the improvement of the students’ ability in writing procedure text.